ERP software selection model for small and medium-sized in retail sector using analytic network process - Hermawan, Ilham Setya; Euis, Nina Saparina Yuliani; Zulfa Fitri, Ikatrinasari (Penerbit Universiti Kebangsaan Malaysia, 2019)
Small and medium sized (SME) retailers strive to maintain the balance of demand and supply in their stores. By maintaining the availability of items, they able to provide positive shopping experience for customers. Therefore, they are able to survive in a competition with large retailers. The technological advances and the shopping behavior are among the factors that encourage SME retailers to adopt the technology information system for supports information between business functions to keep the balance of supply, demand and their distribution. One of the many ways to maintain balance of demand and supply is by implementing Enterprise Resource Planning (ERP) (). However, ERP is quite difficult for SME retailers to be implemented in their organization. Selecting the optimal ERP software is a critical process in the early phase of an ERP project. This study aimed to investigating the priority (preference) of the criteria and alternatives using the Analytic Network Process (ANP) approach for the small and medium-sized retailers focusing in Jakarta. This study conducted by observation and interviews with the experts who have experience with ERP and small and medium-sized retailers. In this study, the pairwise comparisons used to assess the proposed alternatives and criteria. Furthermore, this study also calculates the overall score of the criteria and alternatives for analyzing the relation and preference of the criteria and alternatives. The theory of ANP used to evaluate all criteria and alternatives with expressed numerically. The findings of this study provide an overview that small and medium-sized retail companies tend to require systems or ERP software. In this study, there are 5 criteria most preferred: ease of customization, technical aspects, functionality and compatibility with other systems, and software prices. These criteria are considered to ensure the good operational activities. The most preferred alternative is SAP Business One, as it scored highest on several criteria, Odoo and Acumatica. The limitation of this study is that this study only used three ERP software programs as alternatives and this study focuses only for the small and medium-sized retailers in Jakarta.